ANALISIS PENGARUH PENYALURAN KREDIT USAHA RAKYAT TERHADAP PROFITABILITAS BANK PENYALUR KUR DI INDONESIA - Maria Ariesta Utha; Abubakar Arif; Heti Budisusetyo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
The background of this research is to analyze the effect of channeling the People's Business Credit to the profitability of banks in Indonesfa the People's Business Credit. This study uses quantitative data. The population in this study are listed Bank banking sector. Sampling was done by purposive sampling criterion is the People 's Business Credit bank so that in this study only uses five the People 's Business Credit bank from 2008 until 2010 . The number of observations in this study was 60. The method of analysis was conducted using Structural Equation Model. Results obtained are partial to the first direct effect Public Credit no significant effect on non-performing loons , the People's Business Credit positive and significant effect on the Loan to Deposit Ratio and Capital Adequacy Ratio . For both the direct effect of the non-performing loans and a significant negative impact on Return on Equity and Loan to Deposit Ratio positive and significant impact on the Return on Equity, Capital Adequacy Ratio whereas no significant effect on the Return to Equity. For indirect effects are indirect influence on the Public Credit positively Profitability